Targeted epigenetic silencing of UCHL1 expression suppresses collagen-1 production in human lung epithelial cells. Issue 1 (31st December 2023) - Wu, Dan-Dan; Lau, Andy T. Y.; Xu, Yan-Ming; Reinders-Luinge, Marjan; Koncz, Mihaly; Kiss, Antal; Timens, Wim; Rots, Marianne G.; Hylkema, Machteld N.
ABSTRACT: Ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) is highly expressed in smokers, but little is known about the molecular mechanism of UCHL1 in airway epithelium and its possible role in affecting extracellular matrix (ECM) remodelling in the underlying submucosa. Since cigarette smoking is a major cause of lung diseases, we studied its effect on UCHL1 expression and DNA methylation patterns in human bronchial epithelial cells, obtained after laser capture micro-dissection (LCM) or isolated from residual tracheal/main stem bronchial tissue. Targeted regulation of UCHL1 expression via CRISPR/dCas9 based-epigenetic editing was used to explore the function of UCHL1 in lung epithelium. Our results show that cigarette smoke extract (CSE) stimulated the expression of UCHL1 in vitro . The methylation status of the UCHL1 gene was negatively associated with UCHL1 transcription in LCM-obtained airway epithelium at specific sites. Treatment with a UCHL1 inhibitor showed that the TGF-β1-induced upregulation of the ECM gene COL1A1 can be prevented by the inhibition of UCHL1 activity in cell lines. Furthermore, upon downregulation of UCHL1 by epigenetic editing using CRISPR/dCas-EZH2, mRNA expression of COL1A1 and fibronectin was reduced. In conclusion, we confirmed higher UCHL1 expression in current smokers compared to non- and ex-smokers, and induced downregulation of UCHL1 by epigenetic editing. The subsequent repression of genes encoding ECM proteins suggest a role for UCHL1 as a therapeutic target in fibrosis-related disease.